Advances in micro interfacial phenomena of adsorptive micellar flocculation: Principles and application for water treatment. (1st September 2021) - Demissie, Hailu; Lu, Sen; Jiao, Ruyuan; Liu, Libing; Xiang, Yu; Ritigala, Tharindu; Ajibade, Fidelis Odedishemi; Mihiranga, H.K.M.; An, Guangyu; Wang, Dongsheng
Highlights: The basic principles/advances in adsorptive micellar flocculation (AMF) are summarized. Interfacial phenomena and AMF process applied in water treatment are highlighted. Factors affecting the performance of AMF are comprehensively discussed. Emphasis is given to alternative surfactants and materials recycling/recovery. Ways to enhance AMF efficiency and the future developing prospect are discussed. Abstract: Among various aqua remediation technologies, separation aims at cleaning pollutants by isolating them despite their destruction; solutes can also be recovered after the process. Adsorptive micellar flocculation (AMF) has been known as an important surfactant-based technique to separate poorly water-soluble hazardous pollutants from aqua media as an efficient and energy-intensive replacement for other surfactant-based techniques, as such AMF should be known. AMF is based on the partitioning of solutes gradient from bulk solution into the nanosized smart anionic surfactant micelle followed by flocculation. However, unlike coagulation/flocculation or adsorption, AMF is not viable for the production of drinking water in water utilities due to the loss of surfactant monomers. Unfortunately, it can be used as a reservoir or for the recycling/recovery of organic pollutants (intermediates) (ions, organics/bioactive, dyes, etc.), even at high concentrations. The performance of AMF depends on various parameters, and this review briefly summarizes the existing researches on different pollutants removal by AMF and material recovery/recycling. This includes operating condition factors (surfactants, flocculants, surfactant-flocculant or surfactant-pollutant concentration ratio, and water conditions chemistry). Because varieties of micro interfacial phenomena other than physical interactions occur in a versatile micellar environment in the AMF process, emphases are given to adsorptive oxidation, micellar catalysis, selectivity. Furthermore, for the first time, this review gives an overview of understanding the state-of-the-art multifunctional nano amphiphile-based AMF that behaves mimetic to aquatic organisms in the process of pollutant removal. The efficiency of AMF, including recycling concentrated solution without noticeable deterioration, as an auxiliary resource/income for the next cycle, signifies economic viability, versatility, and manifold applications in aqua remediation. Significance, ways to achieve enhanced process efficiency, as well as challenges and future opportunities in wastewater treatment, are also highlighted. Graphical abstract: Image, graphical abstract